Water Use Efficiency: A Review of Contextual and Behavioral Factors - Callejas Moncaleano, Diana Carolina; Pande, Saket; Rietveld, Luuk (Frontiers in Water, 2021)
Water withdrawals around the world have increased almost twice as fast as the population during the last century. Higher than expected water demand is leading to water scarcity and causing rapid depletion of water tables around the world. One reason behind the higher than expected demand is the inefficient use of water. Inefficient use of water affects the well-being of society, the economic stability of countries, and environmental health. Indeed, water use efficiency (WUE) is one of the pillars of sustainable development goals (SDG 6.4.1). However, progress towards achieving WUE is slow, especially for many developing countries where the degradation of natural resources is critical, economic growth is slow, and there are few strong institutions to coordinate actions. One reason behind inefficient water use is human behaviour. A variety of contextual and psychological factors underlie the behaviour. The contextual factors include socioeconomic, technical, institutional and environmental factors and the behavioural factors include factors associated with the perception of risk, attitudes, norms etc. Yet, few studies consider an integrated view of these factors in shaping water use behaviour. This paper consolidates contextual and behavioural factors which influence water use, studies the gaps in our understanding of human water behaviour underlying WUE and highlights the need to comprehensive assess and consistently measure such factors and their relationships. Based on the gaps identified, it proposes a conceptual model that connects contextual and behavioural factors and represents potential cause-effect relationships as supported by various environmental behaviour approaches and psychological theories. Based on the literature review of water use, and conservation behaviour, environmental psychology, and water use models, this model proposes an institutional factor to assess the relationship between institutions and stakeholders, and study contextual factors linked not only for individual water users but also studying these factors for individuals of water supply organizations.